Muslim migration to the west: the case of the Muslim minority in India - Subhani, Zulqernain Haider; Tajuddin, Nor Azlin; Mohamad Diah, Nurazzura (IIUM Press, International Islamic University Malaysia, 2018)
International migration has drawn much attention from social scientists in recent decades and large-scale migration has become a permanent and substantive part of global socio-economic development. There are many kinds of migration, from refugees to skilled migrants. The migration of highly skilled people from developing to developed countries is known as the brain drain, a form of diaspora based on high education, skills and talents that has been a major point of discussion among different disciplines in the social sciences. India has a very long history of high-skilled migration, being one of the top three sources of migration today. This paper aims to reveal the Muslim brain drain among Indian Muslims since the abolition of ‘License Raj’ in 1990. To understand the patterns of brain drain among Indian Muslims, literature searches were conducted to obtain relevant data in two ways: (1) describing the nature and consequences of brain drain on both home and host countries; and (2) delineating the push-pull factors that lead high skilled individuals to migrate to developed countries. The findings revealed that many Muslims from India have migrated to UK and US over the last three decades. Indian Muslims constitute a very considerable proportion of population in the above-mentioned countries, with a net population of about 200,000 in the UK, and in the US 4% of the total Muslim population are Indian Muslims. Indian Muslim brain drain is driven more by push-factors in India, including religious discrimination and corruption in the public sector, alongside pull-factors in the West, like political stability, economic development, better career opportunity, high wages and balanced workload. Finally, the study indicates that data available on brain drain from various aspects are insufficient. More studies are needed to increase the understanding of migration, which is now becoming more complex among the Muslim communities.